Exploring advanced technologies for the future combat systems program - Matsumura, John (Rand, 2002)
An assessment of technologies, tactics and operational concepts being considered for future army rapid-reaction forces in the USA. It focuses on small-scale contingency and the associated spectrum of challenges that this type of scenario might entail.